Дослiдження горiння крапель парафiну - Orlovskaya, S. G.; Kalinchak, V. V.; Shkoropado, M. S.; Karimova, F. F.; Chernyak, V. Ya.; Vergun, O. Y. (Publishing house "Academperiodika", 2018)
The burning characteristics of pure n-alkanes (n-octadecane and n-docosane) are investigated. Combustion of single and double droplets is studied experimentally, the histories of burning droplets are obtained, and the burning rate constants are determined. Flame transfer is studied in a two- droplet system.